Service Time Improvement Proposition For Insurance Customer Operation At Bpjs Kesehatan West Bandung Office: A Discrete Event Simulation Approach - Rizka Utami Sri Hajarismala; Meditya Wasesa (Cakrawala Repositori IMWI, 2023)
BPJS Kesehatan is one of the public legal entities in Indonesia and provides public services to the public, one of which is the administration process service and the provision of face-to-face information directly to the nearest BPJS Kesehatan office. The Customer Satisfaction Index is an assessment of whether the services provided by BPJS Kesehatan are in accordance with participants' expectations. To create excellent service for participants, BPJS Kesehatan refers to 5 dimensions of service quality, namely Tangibility, Empathy, Responsiveness, Reliability, and Assurance. One of the face-to-face service problems faced by BPJS Kesehatan West Bandung Office every day is the waiting time and long queues. This problem was even listed on the Customer Satisfaction Index as one of the participants' dissatisfaction points. To find out what causes long queues and the long waiting time for participants, interviews, and observations of conditions in the field are needed. This can be searched in a structured manner using Fishbone Analysis. To help find solutions to these problems, we use Discrete Event Simulation in the Anylogic application to analyze the existing service conditions and find alternative solutions to solve the issue. As a result, we propose several alternative operational scenarios and define the best scenario that can be applied to increase CSI and reduce participant complaints about waiting times and long queues.